The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1161/hypertensionaha.114.04521
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Testosterone Exposure Induces Hypertension in Adult Females via Androgen Receptor–Dependent Protein Kinase Cδ–Mediated Mechanism

Abstract: Prenatal exposure to excess testosterone induces hyperandrogenism in adult females and predisposes them to hypertension. We tested whether androgens induce hypertension through transcriptional regulation and signaling of protein kinase C (PKC) in the mesenteric arteries. Pregnant Sprague-Dawley rats were injected with vehicle or testosterone propionate (0.5mg/kg/day from gestation day 15–19, subcutaneously) and their 6-month-old adult female offspring were examined. Plasma testosterone levels (0.84±0.04 vs 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 61 publications
(59 reference statements)
4
29
0
Order By: Relevance
“…T 0 induced blood vessel damage and subsequent hypertension through a PKCδ (activation of protein kinase C δ)-dependent pathway and increased vascular responses to vasoconstrictor agents, such as arachidonic acid and norepinephrine in rats. 37,38 However, estrogens have been reported to be potent vasodilators that lead to an increase in blood flow in selected organs, with the greatest response in the uterus. 39 During mammalian pregnancy, adequate blood supply to the uterine-placental region is crucial to meeting the growing requirement of the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T 0 induced blood vessel damage and subsequent hypertension through a PKCδ (activation of protein kinase C δ)-dependent pathway and increased vascular responses to vasoconstrictor agents, such as arachidonic acid and norepinephrine in rats. 37,38 However, estrogens have been reported to be potent vasodilators that lead to an increase in blood flow in selected organs, with the greatest response in the uterus. 39 During mammalian pregnancy, adequate blood supply to the uterine-placental region is crucial to meeting the growing requirement of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…The relative density of each specific molecule was measured by 36 densitometry, and its value was compared with the GAPDH or -actin value from the same blot. 37 Immunohistochemistry 38 The tissues were fixed in 4% paraformaldehyde (PFA), gradually dehydrated in ethanol and 39 embedded in paraffin wax. The 5-μm-thick paraffin sections were subjected to routine 40 rehydration and antigen retrieval before being incubated with the appropriate antibody.…”
Section: Sources Of Fundingmentioning
confidence: 99%
“…85–23, revised 1996). As we described earlier, 31;43;46;47 timed pregnant Sprague-Dawley rats (gestational day [GD] 12; presence of copulation plug is day 1), purchased from Charles River (Wilmington, MA), were used in this study. After acclimatization, on GD 14, dams were randomly divided into 2 groups.…”
Section: Methodsmentioning
confidence: 99%
“…Blesson and colleagues recently reported that prenatal testosterone excess programs an increase in blood pressure associated with an elevation in testosterone in female offspring mimicking the pathogenesis of polycystic ovary syndrome ( PCOS ) (43). This study published in Hypertension demonstrated that chronic blockade of the androgen receptor with flutamide abolished the programmed increase in blood pressure in the prenatal testosterone exposed female offspring (43) implicating an important role for hyperandrogenism in the pathogenesis of hypertension in this model (43). It is well established that protein kinase C ( PKC ) isoforms modulate vascular activity.…”
Section: Sex Steroids the Renin Angiotensin System And The Developmmentioning
confidence: 99%